Faktor Keengganan Pengguna Jasa Tol Beralih Menggunakan E-Money - Rosanti, Novita; Mustafa, Meizar (Patria Artha University, 2018)
The objective to be achieved is to know what factors make the toll service users reluctantto switch to using e-money. Contributions in this study are expected to provideinformation to Bank Indonesia in establishing policies related to financial transactions inIndonesia. The clan service party as the manager of the toll road and the addition of thesciences rationality in the field of marketing is mainly related to consumer behavior inchoosing a particular product.This study uses primary data with data collection techniques through questionnairemethod. The respondent used is the user of motorway owner of Group 1 vehicle. Furtherdata is processed using Factor Analysis with the help of Statistical Package for the SocialScience (SPSS) version 24 for Windows. Previously tested the instrument with validityand reliability test.The results showed that there are 4 factors that make the toll users are reluctant to switchto using e-money. These factors are the main general behavior factor of a person relatedto individual factor with eigen value 5,364, perception factor with eigen value 1,585,infrastructure factor with eigen value 1,396 and factor of information with eigen value1,034.